Suplemetasi Vitamin E dalam Cairan Rumen In Vitro: Analisis Parameter Fermentasi - Firman Nasiu (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
The aim of this study was to examine the effect of vitamin E on fermentation parameters by using an in vitro fermentation system with ruminal fluid from male Bligon goats. Substrats used in fermentation process comprised of 65% of king grass, 20% of rice bran, and 15% of soybean meal, with additional 3% of capsulated crude palm oil (CCPO). Treatments of an in vitro fermentation were divided into 3 groups, those are group without vitamin E supplementation (R0), group with 200 mg per kg DM vitamin E supplementation (R1), and 400 mg vitamin E supplementation (R2). All groups were incubated for 48 hours according to Menke and Steingass method. Results showed that vitamin E supplementation at the level of 400 mg did not affect fermentation parameters (VFA, NH3, and pH) on ruminal fluid.